Human Papillomavirus Type 16 Disables the Increased Natural Killer Cells in Early Lesions of the Cervix. (28th April 2019) - Zhang, Jiexin; Jin, Shanshan; Li, Xiao; Liu, Lenan; Xi, Lei; Wang, Fang; Zhang, Shichang
Abstract : The mechanism for pathogenesis of human papillomavirus (HPV) in the cervix has been investigated intensively. However, detailed differences in the distribution and function of innate immune cells between high-risk HPV types, especially during the chronic inflammation phase, have not been described fully. In this study, histologic pathology results of 245 women with HPV type 16 only (HPV16 + ) or type 18 only (HPV18 + ) were analyzed retrospectively from January 2015 to November 2016. More severe lesions of the cervix were observed in HPV16 + women compared with those in HPV18 + women. In total, 212 cervical brush specimens were collected from women suffering from chronic inflammation, HPV16 +, or HPV18 + from December 2016 to December 2018. Flow cytometry analysis showed that abundant NK cells along with aberrant Treg cells were found in the HPV16-infected cervix. Quantitative real-time PCR demonstrated that higher expression levels of IFN- γ but muted IL-2 and KLRG-1 expression was detected in the cervix of patients with HPV16 + compared to HPV18 +, which were further confirmed using 20 paraffin sections of cervical conization tissue. The ex vivo cytotoxicity experiment showed that the cytotoxicity of NK cells was significantly decreased in the cervix of HPV16 + patients compared with that of HPV18 + patients. Collectively, our results suggested that HPV16 disables the increased NK cells in the early lesion of the cervix, indicating that the local immune system of the cervix is hyporesponsive to HPV16 infection and this may explain its bias for malignant transformation.